Genetic characterization of sunflower breeding resources from Argentina: assessing diversity in key open-pollinated and composite populations - Moreno, Maria Valeria; Nishinakamasu, Veronica; Loray, M.A.; Alvarez, Daniel; Gieco, Jorge Omar; Hopp, Horacio Esteban; Heinz, Ruth Amelia; Paniego, Norma Beatriz; Lia, Veronica Viviana (Cambridge University Press, 2024)
Open-pollinated (OPs) and composite populations (CPs) represent a valuable resource for sunflower breeding programmes. However, little is known about the levels and distribution of genetic variation within each of these populations. In this study, quantitative and qualitative traits along with molecular markers were used to evaluate 14 populations from the Instituto Nacional de Tecnologı´a Agropecuaria (INTA) sunflower germplasm collection. These populations were chosen to represent historically important accessions that still play a central role within the INTA sunflower breeding programme due to their extensive variation in diverse agronomically important traits. Nine quantitative and eight qualitative agro-morphological descriptors were recorded and compared with those of a larger set of accessions representative of the phenotypic diversity of the sunflower collection. Molecular characterization was conducted on a total of 311 individuals using 16 microsatellite markers. Overall, the average gene diversity was 0.56 and the average number of alleles per locus was 6.25. No statistically significant differences in genetic diversity were detected between the OPs and CPs. Global estimates of FST revealed very high levels of differentiation among accessions (FST ¼ 0.413, P , 0.05). Population structure analyses were consistent with the observed levels of differentiation and identified two major groups. The results of this work show that high global diversity is preserved within the accessions analysed here. Additionally, this study provides a set of reliable and discriminant markers for the cost-effective molecular characterization of sunflower accessions, along with the guidelines for the delineation of sampling strategies for OPs and CPs, thus aiding the efficient management and exploitation of sunflower germplasm collections.